A comparative study of the use of the Istanbul Protocol amongst civil society organizations in low-income countries - Kelly, Tobias; Jensen, Steffen; Andersen, Morten Koch; Christiansen, Catrine; Sharma, Jeevan Raj (Torture Journal, 2018)
The Istanbul Protocol (IP) is one of the great success stories of the global anti-torture movement, setting out universal guidelines for the production of rigorous, objective and reliable evidence about allegations of torture and ill-treatment. The IP is explicitly designed to outline ‘minimum standards for States’. However, it is all too often left to civil society organizations to investigate allegations of torture and ill-treatment. In this context, important questions remain as to how and where the IP can be used best by such organizations. These questions are particularly acute in situations where human rights groups may have limited institutional capacity. This paper explores the practical challenges faced by civil society in using the IP in Low-Income Countries. It is based on qualitative research in three case studies: Nepal, Kenya, and Bangladesh. This research involved over 80 interviews with human rights practitioners. The conclusions of the paper are that the Istanbul Protocol provides a useful framework for documentation, but more comprehensive forms of documentation will often be limited to a very small – albeit important - number of legal cases. In many cases, the creation of precise and standardized forms of evidence is not necessarily the most effective form of documentation for redress or accountability. In the absence of legal systems willing and able to respond effectively to allegations of torture and ill-treatment, there are severe limitations on the practical effectiveness of detailed and technical forms of documentation.